Distribution diversity and expression regulation of class 1 integron promoters in clinical isolates of Morganella morganii - Ye Yang; Hui Zhang; Rongqing Zhao; Xuedan Qiu; Jinglu Ye; Wenjun Lu; Qingcao Li; Guangliang Wu (Frontiers in Microbiology)
BackgroundMorganella morganii is an emerging nosocomial opportunistic pathogen with increasing multidrug resistance. Antibiotic resistance, driven primarily by the horizontal transfer of resistance genes, has become a global health crisis. Integrons, mobile genetic elements, are now understood to facilitate the transfer of these genes, contributing to the rapid proliferation of resistant strains. Understanding the regulatory role of integrons in drug resistance gene expression is crucial for developing novel strategies to combat this pressing public health issue.ObjectiveTo investigate the distribution of promoter types in the variable regions of class 1 integrons isolated from clinical isolates of M. morganii and their regulatory role in the expression of downstream drug resistance gene cassettes.MethodsNinety seven clinical isolates of M. morganii were screened for the presence of class 1 integrons (intI1) using polymerase chain reaction (PCR). Gene cassettes within the variable regions of positive isolates were characterized, and the gene cassette promoter Pc variants and downstream auxiliary promoter P2 were identified. Enterobacterial repetitive intergenic consensus (ERIC)-PCR was employed for homology analysis. Recombinant plasmids containing different variable region promoters and gene cassettes were constructed to evaluate drug resistance genes and integrase (intI1) expression levels using reverse transcription-quantitative PCR (RT-qPCR) and antimicrobial susceptibility testing.ResultsOf the clinical isolates, 28.9% (n = 28/97) were positive for class 1 integrons. 24.7% (n = 24/97) of these isolates carried gene cassettes encoding resistance to aminoglycosides and trimethoprim. Three Pc promoter types (PcH1, PcS, and PcW) were identified, while all P2 promoters were inactive with a 14-base pair spacing between the −35 and −10 regions. ERIC-PCR analysis classified the integron-positive strains into 6 genotypes, with high consistency in promoter types and gene cassettes within each genotype. RT-qPCR and antimicrobial susceptibility testing demonstrated that strong promoters significantly enhanced the expression of downstream drug resistance gene cassettes compared to weak promoters. Additionally, RT-qPCR revealed a negative correlation between intI1 expression and Pc promoter strength.ConclusionClass 1 integrons are prevalent in M. morganii. The promoter types within these integrons are diverse, and promoter strength is closely linked to downstream gene cassette expression. Integron-positive strains exhibit high homology, suggesting horizontal gene transfer and dissemination in clinical settings.